ISSUES OF PREPARATION FOR INCLUSIVE EDUCATION IN THE PROCESS OF INDEPENDENT LEARNING (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the theoretical and practical dimensions of preparing pre-service teachers to work in inclusive educational settings, with particular emphasis on the role and significance of independent learning in this preparation process. The study investigates students' levels of readiness for inclusive education, their existing professional competencies, and their independent learning skills. The article analyzes the essence of the concept of inclusive education, its implementation within the educational system of the Republic of Uzbekistan, and the pedagogical conditions necessary for preparing pre-service teachers to perform effectively in inclusive environments through independent learning. The findings of the research demonstrate that independent learning constitutes an effective means of forming inclusive competencies in pre-service teachers, fostering their professional autonomy, reflective thinking, and creative approach to pedagogical practice. The article proposes a comprehensive program for preparing pre-service teachers for inclusive education.